Pengembangan Media Pembelajaran Berbasis Animasi Interaktif Untuk Materi Hardware Komputer Di SMP PUSTEK Serpong - Angga Suryadi; Nasrul Hidayah (Journal of Research and Publication Innovation, 2024)
Computer hardware is one of the essential subjects in Information and Communication Technology (ICT) taught from elementary to secondary levels. However, teaching computer hardware often faces challenges, such as limited hardware resources and students' busy schedules. Most students find it difficult to understand the broad and diverse concepts of computer hardware.To overcome these challenges, innovative teaching approaches are needed. One effective approach is the use of interactive learning animations. Interactive learning animations combine multimedia elements, such as text, images, animations, and sound, to create an engaging and effective learning experience.This research proposes the development of interactive animation-based learning media for computer hardware materials at SMP PUSTEK Serpong. This learning media is designed to provide clear explanations about computer devices, from input devices to peripherals, and includes practice exercises. The use of Adobe Animate as a development tool allows for easy integration of multimedia elements.The results of this research are expected to increase students' interest in learning about computer hardware and facilitate the learning process for teachers. Additionally, this research provides insights into the use of interactive animations in education, which can be applied across various subjects and educational levels. Thus, the development of interactive animation-based learning media has the potential to enhance the quality of education at SMP PUSTEK Serpong.